Dampak Penerapan Circuit Training Melalui Model Periodisasi Reverse Terhadap Peningkatan Kemampuan Power Endurance - Tri Ummi Kalsum Wulandari; Dikdik Zafar Sidik; Kardjono Kardjono (Jurnal Kepelatihan Olahraga, 2022)
The purpose of this study was to determine the impact of implementing circuit training through the reverse periodization model on increasing endurance. The research method used is an experimental method using One Group Pre-test Post-test Design. Purposive Sampling was used for sampling as many as 14 samples from UPI female futsal players. The sample did a Pre-test to determine the Power Endurance of each sample, then they were treated with 12 meetings for 4 weeks with Circuit Training, after that the sample did a Post-test to determine the effect of the Treatment. The data processing technique used descriptive data analysis, normality test, homogeneity test, and Paired Sample T-Test test. Research data that has been obtained and analyzed using the Paired Sampe TTest test with the IBM SPSS version 25.0 computer application. The results of the analysis show that there is a significant increase in the impact of the application of the reverse periodization model on increasing the power endurance ability with a sig value. 0.00 0.05. it can be said that there is a significant increase in the impact of implementing circuit training through the reverse periodization model on increasing power endurance capabilities.